PENGARUH PENGETAHUAN, MODAL, DAN RISIKO INVESTASI TERHADAP MINAT INVESTAS MAHASISWA (Studi pada Mahasiswa Perbankan Syariah UIN Fatmawati Sukarno Bengkulu) - Huzaifah Aulia; Supardi Mursalin; Rizky Hariyadi (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine how much influence knowledge, capital, and investment risk have on students' investment demand. The population in this study is all Sharia Banking students of UIN Fatmawati Sukarno Bengkulu. With a sample of 86 students. The research method uses quantitative methods with an associative quantitative approach. The research instrument used is by distributing questionnaires. This research data analysis technique is multiple linear regression to test the research hypothesis using t test and f test using SPSS 16 For Windows Software application. The results showed that the variables of knowledge (X1), capital (X2), and investment risk (X3) had a positive and significant influence on students' investment interest. So it can be said that the hypothesis is accepted.